ANALYSIS OF DIGITAL LITERACY UNDERSTANDING OF STUDENTS OF MAHKOTA TRICOM UNGGUL UNIVERSITY TOWARDS DIGITAL SKILLS AND DIGITAL SAFETY - Nidya Banuari; Deby Siska Oktavia Pasaribu; Rhiana Handini (ZILLZELL MEDIA PRIMA, 2023)
The rapid development of digitalization makes it possible to open up information with various digital communication facilities or digital literacy. In the world of education, universities, especially Mahkota Tricom Unggul University, must be able to keep up with current developments in digitalization to be able to produce quality, professional and innovative graduates with international standard capacity and technology-based entrepreneurship skills. In facing society 5.0, the role of students is really needed to be able to understand digital literacy, digital skills and digital safety. The aim of this research is to see how students' digital literacy understanding of digital skills and digital safety adapts to the era of society 5.0. The research will be carried out with a simple survey by applying a questionnaire as quantitative data and the research results will be described descriptively. The respondents will be taken from all active students of the Faculty of Social Sciences, totaling 110 people. The test results show that digital literacy has a positive and significant effect on digital skills with a percentage of 66.2%. And the test results show that digital literacy has a positive and significant effect on digital skafety with a percentage of 72.6%. Thus, it can be said that students' understanding through digital literacy can influence the digital skills and digital safety of students at Mahkota Tricom Unggul University.